PENGARUH PERSEPSI PRODUK DAN AKTIVITAS KOMUNIKASI WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN PRODUK XIAOMI PADA MAHASISWA ILMU KOMUNIKASI REGULER FISIP UNIVERSITAS SEBELAS MARET SURAKARTA - Dian Esti Nurati, Muhammad Rizki, Nurnawati Hindra Hastuti & (Transformasi, 2017)
Xiaomi is one of the products vendor smartphone from china was rising celebrity. The use ofsmartphone Xiaomi start much demanded by marked by the phenomenon smartphone otherbrands switch to smartphone brand Xiaomi likely caused by persuasive communication word ofmouth and perception users of that product. With the owned smartphone Xiaomi able to attractconsumers. This research aims to prove a positive influence products perception andcommunications activity of ‘word of mouth’ against the decision of the use of products amongstudents the regular science of communication sosial science faculty of Sebelas Maret universitysurakarta. The kind of research is eksplanatory research and sample totaled 79 people. Obtainedthe results of the analysis that the perception products and communication word of mouthinfluential positive with significant high against the decision of the use of the product Xiaomi.Key words: products perception, word of mouth communication, the decision of using xiaomiproducts